LEARNING AND REVIEWING VOCABULARY THROUGH MEMRISE TO IMPROVE STUDENTS’ VOCABULARY ACHIEVEMENT - Dian Fadhilawati (Universitas Islam Balitar, 2016)
This article dealt with classroom Action Research which intended to improve the vocabulary achievement of 39-second semester students of Faculty of Agriculture and Animal Husbandry at the Islamic University of Balitar by using Memrise. In this research, the students learned 3 levels of agriculture and vocabulary prepared and created by the lecturer in www.memrise.com. In order to have a good vocabulary achievement, the students are asked to learn the vocabulary in the classroom and review it at home through Memrise Application. The data of the research were collected from tests and questionnaire. This research was conducted in one cycle of action which covered (1) Planning, (2) Acting, (3) Observing and (4) Reflecting. The result of the research showed that the implementation of Memrise as learning and reviewing vocabulary tool could improve the students ’ vocabulary achievement from the mean score 60.45 (Pre-test) to 86.27 (Post-test). Moreover, the result of the research was strengthened by the student ’s positive responses toward the use of Memrise as learning and reviewing vocabulary tool as reflected from the result of the questionnaire given. Keywords: Memrise, Learning and Reviewing Vocabulary, Vocabulary Achievement, Action Research. Received: 24 June, 2016; Accepted: 8 September, 2016